THE EFFECTIVENESS OF SOCIAL MEDIA TWITTER @NETFLIXID ON THE MOTIVE TO USE THE PLATFORM NETFLIX VIDEO STREAMING PLATFORM - Safari, Abdul Rizal; Puspadarmaja, Nyoman (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The rapid development of the internet has facilitated easy two-way communication across distances, places, and times through social media platforms such as WhatsApp, Facebook, and Twitter. These platforms enable individuals to connect and communicate using an internet connection. The impact of the internet's development, particularly through social media, varies depending on the context and message delivery. This research aims to determine the effectiveness of messages delivered through tweets by the official Twitter account @NetflixID on the different motives of the audience for using the Netflix streaming platform. The scope of the research includes the effectiveness of tweets, motives for using streaming platforms, and the Uses and Gratification theory. The study sampled 90 followers of the official Twitter account @NetflixID, employing a descriptive quantitative approach with a positivist paradigm. Data was confirmed through Validity and Reliability Tests, and Simple Linear Analysis using IBM SPSS software. The findings indicate that the effectiveness of the @NetflixID Twitter account significantly impacts the motivations for using the Netflix streaming platform. The findings suggest that enhancing the effectiveness of social media communications, specifically through engaging and well-crafted tweets, can significantly influence user motivation and engagement with the Netflix streaming platform.